2018
DOI: 10.1016/j.athoracsur.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Native and Prosthetic Aortic Infection With Xenopericardial Tube Grafts

Abstract: Patients with infectious aortic disease present in a frail state and the initial and the late mortality is substantial. Yet, surgical treatment of native and prosthetic aortic infection with xenopericardial tube grafts shows promising short-term results with regard to durability and freedom from reinfection in any aortic segment. Further studies are needed to learn of the long-term behavior of these grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…There were studies with small case numbers, which have reported the utilization of bovine pericardial grafts as a novel substitution of infected aorta. 26,27 This approach shows promising short-term results, but further studies are needed to evaluate the long-term solidarity of these grafts.…”
Section: Discussionmentioning
confidence: 99%
“…There were studies with small case numbers, which have reported the utilization of bovine pericardial grafts as a novel substitution of infected aorta. 26,27 This approach shows promising short-term results, but further studies are needed to evaluate the long-term solidarity of these grafts.…”
Section: Discussionmentioning
confidence: 99%
“…39,40,44e46,48e50,52e 56,58,59,61,62,65,66,68,70,72,73,76,79e86,90,91,96e98,100,102e109,111,113e 118,120,121,124,127e129,131,132 Sixteen more studies were excluded because they described irrelevant topics other than abdominal AGI. 37,57,60,63,69,74,75,78,87,89,92,112,119,122,123,126 Finally, studies were excluded because of study design (n ¼ 5), 47,51,94,95,125 overlapping data (n ¼ 3), 42,43,99 language (n ¼ 9), 38,41,64,67,71,77,88,101,130 or a MINORS score < 9 (n ¼ 2). 93,110 A flow chart of the selection procedure is shown in Fig.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Self-made tubes of bovine pericardium have been used to replace the ascending aorta and root with promising results. 51,52 When implanting a composite conduit in a fragile aortic annulus, the proximal anastomosis may be reinforced with pericardium. 53 Others have proposed variations of this technique still using pericardium to obtain a doughnut-shaped skirt of bovine pericardium to reinforce the aortic annulus.…”
Section: Valvular and Prosthetic Endocarditismentioning
confidence: 99%
“…Although this device may have definite indications, such as endocarditis or old patient age, nevertheless a word of caution has been raised due to high rate of reoperations warning against its use. 51,52 The use of valved conduits implies many suture lines with the potential for bleeding complications; the weakest points are at the coronary buttons anastomosis and pseudoaneurysm formation has been observed at this level in patients with fragile tissues such as those with dissection of Marfan's syndrome. 63 For such reason, some suggest the routine use of pericardial strips to reinforce these sutures.…”
Section: Surgery Of the Ascending Aortamentioning
confidence: 99%